Analysis of effectiveness and efficiency of rota use integrated filling machine on filling results 2 ml vial - Fenny Kristanti Panggabean; Delina Hasan; Iha Haryani Hatta (Jurnal Info Sains : Informatika dan Sains, 2024)
This study aims to analyze the effectiveness and efficiency the use of Rota Integrated Filling Machine (RIFM) on 2 ml vials at PT. X Jakarta. It is an aimed at providing in-depth insights into the optimization of RIFM usage in the context of filling 2 ml vials. Data analysis in this research includes calculating the OEE, Pareto diagram, cause-andeffect, descriptive analysis, machine depreciation calculation, and one-sample t-test. The study results are the OEE values are 32.35% (low effectiveness) in 2020, 32.68% (low effectiveness) in 2021, and 81.36% (high effectiveness) in 2022. The effectiveness of training for RIFM operators at PT. X Jakarta falls into the good category (> 76 – 100%), indicating that the provided training is effective, although some aspects may need modification. The most frequent (dominant) obstacles during theconsecutive injection production process, from highest to lowest, are filling (62hours), capping (35hours), washing (31hours), and other obstacles (21hours). The depreciation burden in 2022, using the straight-line method without residue is Rp 3,237,907,071; the sum-of-the-years-digits method is Rp 883,065,565; the double declining balance method is Rp 2,512,441,817; the unit of working hours method is Rp 1,607,960,385; and the unit of production output method is Rp 1,619,526,867. Estimating depreciation using the machine's economic life aims to guide further actions that the management should take in managing the company's assets that may affect the company's profit and loss statement.